2007
DOI: 10.1159/000109074
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Exogenous Tissue Factor on the Regulators of Proliferation and Apoptosis in Endothelial Cells

Abstract: Background: The exposure of tissue factor (TF) at the site of injury or trauma is a rapid process that leads to the initiation of blood coagulation as well as homeostatic processes giving rise to vascular repair. Aims and Methods: By exposing human endothelial cells to combinations of exogenous TF and factor VIIa (FVIIa) in serum-free medium, the influence of TF concentrations on cellular proliferation and apoptosis was investigated. Results: Lower concentrations of TF resulted in increased cellular proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 39 publications
4
29
0
Order By: Relevance
“…In contrast, in the absence of estradiol, a low concentration of rTF (1.3 pg/mL) was proliferative, whereas 13 pg/mL rTF was antiproliferative, a phenomenon also observed previously in endothelial cells (14). Interestingly, the activities of both PAR2 and h 1 -integrin seem to be prerequisite for the ability of rTF to suppress estradiol-mediated cell proliferation (Fig.…”
Section: Influence Ofsupporting
confidence: 77%
See 1 more Smart Citation
“…In contrast, in the absence of estradiol, a low concentration of rTF (1.3 pg/mL) was proliferative, whereas 13 pg/mL rTF was antiproliferative, a phenomenon also observed previously in endothelial cells (14). Interestingly, the activities of both PAR2 and h 1 -integrin seem to be prerequisite for the ability of rTF to suppress estradiol-mediated cell proliferation (Fig.…”
Section: Influence Ofsupporting
confidence: 77%
“…Neutralization of the labeled rTF using a polyclonal anti-TF antibody or competition with excess unlabeled rTF abolished the binding of fluoresceinlabeled rTF (Table 1). We have shown previously that rTF binds to the surface of endothelial cells (11,14), which possibly occurs through binding to putative cell receptors capable of interacting with TF (16). Furthermore, rTF appeared to be focused at particular points on the cell membrane as reported previously for endogenous TF (17), suggesting an interaction with specific cell surface proteins also localized to these points.…”
Section: Mol Cancer Res 2008;6(12) December 2008supporting
confidence: 65%
“…It has been described that exogenous TF induces several cellular effects, such as the induction of proliferation, migration, and finally tube formation. 44,45 Our results shown that the proangiogenic activated mECs are able to release TF-bearing mEMPs, which drive other mECs and pericytes to increase new vessel formation.…”
Section: Discussionmentioning
confidence: 72%
“…4 Furthermore, it has been shown that incubation of endothelial cells (EC) with recombinant TF alone induces cellular proliferation, together with an associated upregulation of cyclin D1 expression in these cells. 7 Recently, a number of reports have demonstrated the ability of TF to interact with cell surface integrins, 8 -11 resulting in diverse cellular outcomes, including the activation of cell signaling pathways, cell migration, and capillary tube formation. 8,9,11 The binding of cell surface TF to ␤1-integrin, ␣3-integrin, and ␣6-integrin on endothelial cells was shown to require FVIIa, 9 whereas binding of alternatively spliced TF (asTF) to ␣v␤3-integrin and ␣6␤1-integrin was shown to be independent of FVIIa.…”
mentioning
confidence: 99%
“…Moreover, it was demonstrated that this form of TF interacts with the cell surface. 7,10,21 This study is an attempt to further elucidate the mechanisms by which exogenous TF induces endothelial cell proliferation. Throughout this investigation, 2 forms of "exogenous" TF, lipidated recombinant TF and TF-containing cell-derived microparticles, have been used at concentrations of TF corresponding to those found in healthy individuals (5 to 10 pmol/L) or in plasma of patients with cardiovascular disease (50 to 200 pmol/L).…”
mentioning
confidence: 99%